Moral Horizons of Land and Place. Issue 1 (2nd January 2018) - Stead, Victoria; Dominy, Michèle D.
ABSTRACT: A recent 'moral turn' in anthropology has cast new light on morality as a subject of ethnographic inquiry, and on the making of moral meaning and judgment. This article, and the special issue it prefaces, contribute to this emergent literature through foregrounding and examining the moral dimensions of land and place. Taking up Didier Fassin's injunction for a critical moral anthropology – rather than an anthropology of morality – we look to land and place as groundings for moral challenges and practices that are nevertheless not place-bound. A critical moral anthropology of land and place should be directed, we argue, to the interplay of mobility and emplacement, to the dynamics of landscape and 'dwelling', and to the multiplicities of expectation and meaning that surround the making and exploitation of resources. In contexts of global and local change, land and place offer productive grounds from which to consider the moral horizons – both spatial and temporal – of our world and our discipline.